Generating formal employment in a context of implementation of the Decent Work Agenda: A review over territories Bahian identity - Laumar Neves de Souza; Helcio de Medeiros Junior; Tatiana de Andrade Spinola (European Regional Science Association (ERSA), 2015)
The positive dynamics of the national economy in relation to the generation of jobs formal has been an issue that has generated a great deal of interest in Brazilian society and, consequently, has gained much space in more different vehicles of communication, in the course of the last decade. The challenge in this work is to describe some specific traits of the formal labor market, in the period covering the years 2001 to 2010, prioritizing a form of analysis that assesses the singularities of employment developments with record book signed in the Territories of Bahian Identity. In fact, we tried to build a kind of profile of formal employment in the state, evaluating its evolution over time, identifying especially who is the worker who has entered this market in previous decade, which the level of salary offered, the level of education required, which the sectors that generated jobs and the territories of state identity that most benefited from with new jobs. In spatial terms, a large part of the quota of jobs generated occurred in a small number of municipalities, because according to the information obtained only 27 of a total of 417 cities of Bahia gathered 62.6% of jobs, and the Territories of Identity responsible for 60.2% of the jobs were the Metropolitana de Salvador and the Portal do Sert\~ao, in which the municipalities of Salvador and Feira de Santana, the two largest cities of Bahia, stand out. The existence of a set of investments implemented in Bahia that resulted in an increase in the demand of work did not reach the majority of the territories. The excessive concentration of jobs generated reflects the great inequality of opportunities of employment the worker baiano in relations of higher quality. In general, the largest volume of freshmen in jobs had 18 to 24 years, high school education, realizing wages between 0.51 and 1.5 minimum wage and in companies located in the Identity Territory Metropolitana de Salvador. The workers who disagreed with these parameters, is the personal attributes, residence or expected return (salary range), are only eligible to precarious relations, taking the informality their port of entry into the labor market. For this reason, in according with census data, in 2010 there were more than half of labor relations characterized as informal in Bahia. Therefore, if there is to be an agenda of State that intends to reduce regional inequality and personal opportunities of worker baiano, a proposal which identifies itself with the assumptions of the Decent Work Agenda for the Bahia, this research provides evidence to policymakers a look less cyclical and more structural.
Keywords: J23; J31; J38; 330; economy baiana; formal employment; labor market; territories of identity